Integrasi Muatan Pendidikan Lingkungan Hidup Pada Mata Pelajaran IPA Materi Suhu Dan Kalor Berbantuan Media Video Pembelajaran Praktikum Sederhana Untuk Siswa Kelas V Sekolah Dasar - Mohammad Fahmi Nugraha; Meiliana Nurfitriani; Gumgum Gumi; Andreani Yosiva; Ismail Ismail (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2022)
This study aims to analyze the integration of environmental education content in science subjects on temperature and heat materials with the aid of simple practicum learning video media for fifth grade elementary school students. The method used is a qualitative research method with descriptive analysis techniques with library research by examining the integration of environmental education content in science subjects with temperature and heat material assisted by simple practicum learning video media for fifth grade elementary school students. Data collection is done by reducing documents in the form of reports, news and research articles both nationally and internationally related to the topic of this research article. The results of the study indicate that the integration of environmental education content can be carried out into all subjects in elementary schools, the subjects that are considered the closest to be integrated with environmental education subjects are science subjects which can be given with various kinds of learning approaches, one of which is is to use a simple practical learning approach. By using a simple practicum approach, students are expected to be able to use materials that are easy to find in everyday life to become learning materials. In addition to providing students with an understanding of science materials, this approach also has another value, namely campaigning for students about the 3R (Reduce, Reuse, Recycle) program so that waste production can be reduced. The use of a simple practicum learning approach in science subjects on temperature and heat materials assisted by learning video media is expected to be an answer where in the process the science learning objectives can be achieved and can also create a generation that cares about the environment because they have been accustomed to using simple and recycled materials for the learning process.